Clinical characteristics of severe influenza as a risk factor for febrile seizures in children: a retrospective analysis - Li, Peng; Chen, Mei; Wang, Daobin; Zhang, Xue; Sun, Ruiyang; Jia, Wanyu; Fu, Shuqin; Cui, Junhao; Song, Chunlan (Frontiers in Pediatrics, 2024)
Objective To retrospectively analyze the clinical characteristics and independent risk factors of severe influenza combined with febrile seizures, and to provide more basis for early clinical intervention. Methods A total of 161 children with severe influenza were collected as study subjects and divided into convulsive (FC) group (40 cases) and non-convulsive (NFC) group (121 cases) according to whether they had febrile seizures. The demographic characteristics and clinical data of the two groups were analyzed. Multivariate logistic regression was used to analyze the risk factors of severe influenza combined with febrile seizures. The predictive efficacy was evaluated by receiver operating characteristic (ROC) curve analysis. Results 1. Multiple logistic regression analysis revealed that C-reactive protein (CRP) levels, Serum interleukin 6 (IL-6) levels, Days from onset of Flu symptoms to hospitalization, cerebrospinal fluid protein (CSF-TP) levels and the influenza virus type A (FluA) infection rate were found to be independent risk factors for severe influenza combined with febrile seizures in children. 2. ROC curve analysis showed that the cut-off value of CRP, Serum IL-6, Days from onset of Flu symptoms to hospitalization and CSF-TP were 7.57mg/L, 9.84pg/mL, 4.5d and 194.8mg/L, respectively. Conclusion Children with severe influenza with CRP≥7.57mg/L, Serum IL-6≥9.84pg/mL, Days from onset of Flu symptoms to hospitalization ≤4.5d, CSF-TP≥194.8mg/L and FluA had a significantly increased risk of febrile seizures. It is useful for clinicians to determine the risk of severe influenza combined with febrile seizures, to adjust the early treatment plan, and to reduce the incidence of critically ill patients.